Real-time reliable determination of binding kinetics of DNA hybridization using a multi-channel graphene biosensor - Xu, Shicai; Zhan, Jian; Man, Baoyuan; Jiang, Shouzhen; Yue, Weiwei; Gao, Shoubao; Guo, Chengang; Liu, Hanping; Li, Zhenhua; Wang, Jihua; Zhou, Yaoqi (Nature communications, 2017)
Reliable determination of binding kinetics and affinity of DNA hybridization and single-base mismatches plays an essential role in systems biology, personalized and precision medicine. The standard tools are optical-based sensors that are difficult to operate in low cost and to miniaturize for high-throughput measurement. Biosensors based on nanowire field-effect transistors have been developed, but reliable and cost-effective fabrication remains a challenge. Here, we demonstrate that a graphene single-crystal domain patterned into multiple channels can measure time- and concentration-dependent DNA hybridization kinetics and affinity reliably and sensitively, with a detection limit of 10 pM for DNA. It can distinguish single-base mutations quantitatively in real time. An analytical model is developed to estimate probe density, efficiency of hybridization and the maximum sensor response. The results suggest a promising future for cost-effective, high-throughput screening of drug candidates, genetic variations and disease biomarkers by using an integrated, miniaturized, all-electrical multiplexed, graphene-based DNA array. Monitoring DNA binding and single-base mismatches accurately in real time is difficult, especially for miniaturized devices. Here the authors report a graphene field-effect transistor array capable of reliably measuring DNA hybridization kinetics and affinity at the picomolar level.